PERISTILAHAN DALAM UPACARA PEMBERIAN NAMA BAYI PADA MASYARAKAT DAYAK KANAYATN - Pamurani, Ary; Seli, Sesilia; Amir, Amriani; Simanjuntak, Hotma; Madeten, Sisilya Saman (Universitas Tanjungpura, 2024)
terminology in the baby naming ceremony in the dayak kanayatn community. thesis. indonesia language education study program, departemen of language and arts education, faculty of the theacher training and education, tanjungpura university pontianak. This research terminology of baby naming traditional ceremony uses a descriptive method with a from of qualitave research, which aims to describe the results of the resting form of the baby naming tradisional ceremony (monomorphemic, polymorphemic, and phrase), the meaning of the terminology of the baby naming traditional ceremony (lexical meaning, grammatical meaning, and cultural meaning), and a learning plan of the terminology of the baby naming traditional ceremony in junior high school. The data saurces in this research are the actors in the baby naming traditional ceremony, namely the family (husband, wife, grandmother), celebrants, and ceremony preparation officers. The data obtained from the baby naming traditional ceremony amounted to 21 data, which were categorized based on procession (9 terms); perpetrator (2 terms); tools (1 terms); and materials (9 terms).